Cobalt Doped in Zn‐MOF‐5 Nanoparticles to Regulate Tumor Microenvironment for Tumor Chemo/Chemodynamic Therapy. Issue 16 (20th June 2022) - Gong, Yishu; Leng, Junke; Guo, Zhaoming; Ji, Peijun; Qi, Xiuyu; Meng, Yulan; Song, Xue‐Zhi; Tan, Zhenquan
Abstract: Metal‐organic frameworks are often used as a chemotherapeutic drug carrier due to their diverse metal sites and good acid degradation ability. Herein Co‐doped Zn‐MOF‐5 nanoparticles with a high Co doping rate of 60% were synthesized for chemo‐chemodynamic synergistic therapy of tumor. Co ions can mediate chemodynamic therapy through Fenton‐like reaction and regulate the tumor microenvironment by consuming the reduced glutathione. The CoZn‐MOF‐5 shows high drug loading capacity with doxorubicin loading rate of 72.8%. The CoZn‐MOF‐5@PEG@DOX nanodrugs has a strong killing effect on 4T1 cancer cells, suggesting the chemo‐chemodynamic synergistic effect on tumor therapy. Abstract : CoZn‐MOF‐5@PEG@DOX is synthesized as a drug delivery system with dual responsive release behavior to enhance synergistic chemotherapy‐chemodynamic therapy for tumors.